Optimizing laser powder directed energy deposition for Grade-91 and Grade-92 ferritic/martensitic steels for nuclear applications: linking process parameters to microstructure - Mahmud, Asif; Meher, Subhashish; Renner, Peter; Rieffer, Ariel; Silva, Chinthaka; Snitzer, John; Zhang, Qianwen; Lou, Xiaoyuan; Van Rooyen, Isabella (Frontiers in Nuclear Engineering, 2025)
The nuclear industry is increasingly acknowledging the advantages of additive manufacturing (AM) due to its improved design flexibility and reduced manufacturing steps for producing complex engineering components. This study demonstrates the successful fabrication of nearly fully dense, nuclear-grade Grade-91 and, for the first time, Grade-92 Ferritic/Martensitic (F/M) steels via laser powder directed energy deposition (DED). Through rigorous process optimization, specifically tailoring laser power and scan speed, relative densities exceeding 99.8% were achieved in deposited 10 ×10×12 mm3 blocks, yielding exceptional build quality. The resulting microstructures exhibited a characteristic lath martensite morphology, indicative of the rapid solidification inherent to the DED process. While both alloys showed this general microstructure, the addition of tungsten (W), slightly higher carbon content, and higher geometrically necessary dislocation (GND) density in Grade-92 significantly influences mechanical properties, evidenced by a substantial increase in Vickers hardness (425 ± 12 HV) compared to Grade-91 (386 ± 14 HV). Estimated yield strengths, derived from hardness measurements, were 1063 MPa and 1195 MPa for Grade-91 and Grade-92, respectively. These findings suggest DED as a viable and promising route for manufacturing high-performance F/M steel components tailored for demanding nuclear applications, paving the way for improved reactor designs and enhanced operational efficiency.